2010
DOI: 10.3945/jn.109.115147
|View full text |Cite
|
Sign up to set email alerts
|

All-trans Retinoic Acid Lowers Serum Retinol-Binding Protein 4 Concentrations and Increases Insulin Sensitivity in Diabetic Mice

Abstract: Recent investigations have demonstrated that elevated serum retinol-binding protein 4 (RBP4) secreted from adipose tissue plays a role in the development of systemic insulin resistance, and lowering RBP4 improves insulin sensitivity. These observations provide a rationale for the development of new antidiabetic agents aimed at reducing serum RBP4 concentrations. In this study, we sought to determine whether retinoic acid (RA) administration decreases serum RBP4 and suppresses insulin resistance in diabetic ob/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 45 publications
5
45
1
2
Order By: Relevance
“…[15][16][17][18][19][20][21][22][23][24] On the opposite, in the present study a three-fold excess of vitamin A intake in early life (day 1 to day 20 of life) exacerbated WAT expansion in response to a HF diet later in life. The reason(s) of this apparent discrepancy is unknown but could relate to concentration-dependent effects, because studies in adult animals typically used relatively high retinoid concentrations (reviewed in 10 ).…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…[15][16][17][18][19][20][21][22][23][24] On the opposite, in the present study a three-fold excess of vitamin A intake in early life (day 1 to day 20 of life) exacerbated WAT expansion in response to a HF diet later in life. The reason(s) of this apparent discrepancy is unknown but could relate to concentration-dependent effects, because studies in adult animals typically used relatively high retinoid concentrations (reviewed in 10 ).…”
Section: Discussionmentioning
confidence: 41%
“…9,10 Retinoic acid (RA), its acid form, potently blocks adipogenesis of cultured preadipose cells when introduced at early stages of the differentiation process, 11 although other reports indicate that RA at low doses may in fact promote adipogenesis. [12][13][14] Studies in adult rodents treated with RA [15][16][17][18][19][20][21][22][23] or retinaldehyde 24 sustain an antiadiposity action of vitamin A derivatives in vivo. Furthermore, results from animal studies 16,[25][26][27][28] and human observational studies 29,30 point to an inverse relationship between vitamin A status and body fat content.…”
Section: Introductionmentioning
confidence: 99%
“…Corroborating with the above observations, supplementation of retinoic acid to ob/ob mice reduced plasma RBP4 levels by increasing its renal clearance and thus improving insulin sensitivity (10). Furthermore, genetic polymorphisms in RBP4 are also found to be associated with higher risk of development of T2D (11).…”
Section: Rbp4 and Its Link To Diabetesmentioning
confidence: 54%
“…ERK1/2, p38, and STAT-JAK) or the receptor is being down-regulated leading to impairment of all subsequent pathways. Furthermore, studies have indicated that retinoic acid can induce peroxisome proliferator-activated receptor g (PPARg) and thus lead to an insulin-sensitized cell (Krskova-Tybitanclova et al 2008, Macejova et al 2009, Manolescu et al 2010. We hypothesized that retinoic acid is capable of down-regulating the AT1 itself; if the AT1 is being down-regulated, it may be due to increased insulin sensitivity and increased intracellular glucose uptake.…”
Section: Introductionmentioning
confidence: 99%